Misleading clinical and imaging features in atypical aggressive angiomyxoma of the female vulvovaginal or perianal region: report of three cases and review of the literature - Zhang, Ling; Liu, Rong; Peng, Jian (Frontiers in Oncology, 2024)
Objectives: Aggressive (deep) angiomyxoma (AAM) is a rare mesenchymal tumor that typically originates from the vulvovaginal region, perineum, and pelvis in adult women. The objective of this case report and literature review is to comprehensively analyze the clinical, imaging, and pathological characteristics of atypical AAM in the female lower genital tract and pelvic floor in order to minimize preoperative misdiagnosis or missed diagnosis and ultimately optimize the clinical management strategy.The data of three cases with atypical AAM, which demonstrate similarities with other lesions observed in the female lower genital tract over the past one and a half years, were retrospectively described. This description included clinical management, images and reports of ultrasonography (US) and magnetic resonance imaging (MRI), clinicopathological features, followup, and outcomes. In the discussion section, a review of the literature on MEDLINE (PubMed) and Web of Science from the past fifty years was conducted.The three cases all underwent preoperative ultrasonography, and two of them also underwent preoperative MRI examination. Complete resection of the lesions was performed in all three cases, followed by postoperative pathological examination. The histopathology of these three cases revealed invasive angiomyxoma, as confirmed by immunohistochemical staining which demonstrated positive expression of desmin, vimentin, estrogen and progesterone receptors. The patients experienced a smooth postoperative recovery. Ultrasound had a diagnostic accuracy rate of 100% (3/3) for locating and determining the extent of the lesions; however, its specific diagnostic accuracy rate for identifying the pathological type was only 33% (1/3). On the other hand, MRI had a diagnostic accuracy rate of 100% (2/2) for locating and determining the extent of lesions but did not show any specific diagnostic accuracy for identifying the pathological types.Our findings indicate that even if a vulvovaginal lesion presents with a superficial location, small size, limited scope, and regular shape, suspicion of atypical AAM should arise when palpation reveals toughness, tensility, and deformability under pressure. US reveals a well-defined hypoechoic to anechoic mass with uniformly distributed coarse dot echoes, with or without detectable intratumoral blood flow signal. MRI shows prolonged T1 and T2 signals with inhomogeneous enhancement and evident diffusion restriction on DWI.